OUTCOME OF CERVICAL DISECTOMY AND FUSION WITH STABILIZATION IN SINGLE LEVEL CERVICAL DISC - Raja, Riaz A; Razaq, Muhammad Naeem-ur-; Shaikh, Saleem Ahmad; Khan, Hameed (Journal of Ayub Medical College Abbottabad, 2010)
Background: Cervical radiculopathy is a common and distressing problem. Only those patients who failed conservative treatment should undergo surgery. The anterior cervical disectomy is the procedure which offers maximal exposure of the disc space. It easily removes the portion of disc which compresses the nerve root. Possibility of developing late kyphosis from disc space collapse supported the fusion procedure after single level disectomy. The goal of instrumentation is to provide immediate stability, increase fusion rate, prevent graft failure, improve rehabilitation process and possibly no need for external orthosis. Objective of study was To see the results and complications of cervical disectomy thru anterior approach and fusion and stabilisation with titanium made plate. Methods: This was a prospective study, comprised of 32 patients admitted during period from 2005- 2008. Patients presented with radiculopathy or radiculo-myelopathy were evaluated. MRI was carried out in all the cases. Each patient was carefully evaluated to confirm clinico-radiological correlation and patients with significant disc and failure of conservative treatment were included in the study. Results: Males were 28 (87.5%) and female were 4 (12.5%). Twenty patients (62.5%) were in fourth decade. C5-6 was involved in 18 (56.25%) patients. No significant postoperative complications noted. Persistent neck and back pain noted in patients in disectomy group without plating. Conclusion: Anterior cervical disectomy, fusion and stabilisation with plating is a safe and easy procedure in single level cervical disc disease without significant complications. Keywords: Cervical disectomy, fusion, anterior approach, cervical platting